2016
DOI: 10.1016/j.yrtph.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tobacco Heating System 2.2. Part 7: Systems toxicological assessment of a mentholated version revealed reduced cellular and molecular exposure effects compared with mentholated and non-mentholated cigarette smoke

Abstract: Modified risk tobacco products (MRTPs) are being developed with the aim of reducing smoking-related health risks. The Tobacco Heating System 2.2 (THS2.2) is a candidate MRTP that uses the heat-not-burn principle. Here, systems toxicology approaches were engaged to assess the respiratory effects of mentholated THS2.2 (THS2.2M) in a 90-day rat inhalation study (OECD test guideline 413). The standard endpoints were complemented by transcriptomics and quantitative proteomics analyses of respiratory nasal epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…This cluster contains genes that represent the main branches of the oxidative stress response, namely: the glutathione system (GCLC, GCLM, MGST1, GSR), the thioredoxin system (thioredoxin reductase 1, TXNRD1), the peroxiredoxin system (PRDX1, SRXN1), quinone NAD(P)H dehydrogenase 1 (NQO1), and metabolic adjustments for NAPDH production (glucose-6-phosphate dehydrogenase (G6PD)). A similar impact on the oxidative stress response pathways was observed previously in rat lung tissue exposed to 3R4F CS 56 and in human lung tissue under oxidative stress conditions. 57 59 The altered gene expression in this cluster further showed that THS2.2 aerosol induced a transient oxidative stress response that was limited to the 4 h after exposure time point across all three cultures (an exception was observed for NQO1 in the nasal culture).…”
Section: Resultssupporting
confidence: 85%
“…This cluster contains genes that represent the main branches of the oxidative stress response, namely: the glutathione system (GCLC, GCLM, MGST1, GSR), the thioredoxin system (thioredoxin reductase 1, TXNRD1), the peroxiredoxin system (PRDX1, SRXN1), quinone NAD(P)H dehydrogenase 1 (NQO1), and metabolic adjustments for NAPDH production (glucose-6-phosphate dehydrogenase (G6PD)). A similar impact on the oxidative stress response pathways was observed previously in rat lung tissue exposed to 3R4F CS 56 and in human lung tissue under oxidative stress conditions. 57 59 The altered gene expression in this cluster further showed that THS2.2 aerosol induced a transient oxidative stress response that was limited to the 4 h after exposure time point across all three cultures (an exception was observed for NQO1 in the nasal culture).…”
Section: Resultssupporting
confidence: 85%
“…The tobacco industry has performed multiple studies regarding health consequences of HTP use. The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 94%
“…Following the manufacturer recommendations, especially proper cleaning of the device after each 20 tobacco sticks seems to be crucial to provide proper thermal regulation and reduce emissions of harmful substances. Most of the research regarding the chemical composition of generated aerosol was carried out on brand new, never used devices [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Independent researchers showed that the use of 1 IQOS tobacco stick left a significant amount of debris, fluid, and fragments of cast-leaf in the device holder [8].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…For toxicological assessment, changes in metabolic profiles and their relationship to various biochemical pathways are investigated. Untargeted approaches have been used for this purpose, for instance, to explore the global impact of environmental chemical contaminants on earthworms (Griffith et al 2018 ) or on human cells (Hartung et al 2017 ), or to assess the impact of tobacco exposure on in vitro systems (Iskandar et al 2017 ; Kogel et al 2016 ; Zanetti et al 2017 ). For in vitro toxicology studies, two-dimensional (2D) cell cultures have been the most commonly investigated systems for decades.…”
Section: Introductionmentioning
confidence: 99%